Survey Research for Public Administration. - Folz, Professor David H. (SAGE Publications, 1996)
With opinion surveys being used increasingly to measure the public response to governmental initiatives, this book that helps clarify the basics of survey research as they apply to public administration will be welcomed. It is organized around the fundamental stages of the research process - planning, design, implementation, analysis and presentation of data. David H Folz presents practical illustrations and does not assume the reader to have an extensive background in statistics. Thorough coverage of the use of computers in data analysis is provided, together with illustrations of SPSS.